A Population-Based Study of the Incidence of Delusional Infestation in Olmsted County, Minnesota, 1976–2010 - Bailey, C. H. (Br J Dermatol, 2014)
BACKGROUND: Delusional Infestation (DI) is a well-recognized clinical entity but there is a paucity of reliable data concerning its epidemiology. Knowledge of the epidemiology of disease is fundamental to an understanding of any disease and its implications. Epidemiology is most accurately assessed using population-based studies, which are most generalizable to the wider population in the US and worldwide. No population-based study of the epidemiology (particularly incidence) of DI, that we are aware of, has been reported to date. OBJECTIVES: To determine the incidence of delusional infestation (DI) using a population-based study. METHODS: Medical records of Olmsted County residents were reviewed using the resources of the Rochester Epidemiology Project to confirm the patient’s status as a true incident case of DI and to gather demographic information. Patients with a first-time diagnosis of DI or synonymous conditions between January 1, 1976, and December 31, 2010 were considered incident cases. RESULTS: Of 470 identified possible diagnoses, 64 were true incident cases of DI in this population-based study. The age- and sex-adjusted incidence was 1.9 (95% CI, 1.5–2.4) per 100,000 person-years. Mean age at diagnosis was 61.4 years (range, 9–92 years). The incidence of DI increased over the 4 decades from 1.6 (95% CI, 0.6–2.6) per 100,000 person-years in 1976–1985 to 2.6 (95% CI, 1.4–3.8) per 100,000 person-years in 2006–2010. CONCLUSIONS: In this population-based study of the incidence of DI, the age- and sex-adjusted rate was 1.9 per 100,000 person-years.